Mapping the Relationships Among Basic Facts, Concepts and Application, and Common Core Curriculum-Based Mathematics Measures. Issue 1 (1st March 2016) - Codding, Robin S.; Mercer, Sterett; Connell, James; Fiorello, Catherine; Kleinert, Whitney
Abstract: There is a paucity of evidence supporting the use of curriculum-based mathematics measures (M-CBMs) at the middle school level, which makes data-based decisions challenging for school professionals. The purpose of this study was to examine the relationships among three existing M-CBM indices: (a) basic facts, (b) concepts/application, and (c) measures aligned with Common Core. In a sample of 408 sixth, seventh, and eighth graders, cross-lagged panel analyses were used to examine the temporal relationships of the M-CBM indices over three screening occasions. Latent growth models were also used to investigate (a) patterns of annual growth on the indices and (b) predictive validity of M-CBM level and slope on a high-stakes state assessment. Results indicated that (a) concepts/application scores predicted change in the Common Core measure with mixed evidence that basic facts predicted change on the concepts/application and Common Core tools; (b) growth was positive in all grades but nonlinear in some grades; and (c) fall scores on all measures, but only slopes on the Common Core tool, were related to performance on the high-stakes assessment.